Challenges of ICT Tools for Managerial Functions in Private Secondary Schools - Abdulrahim, Abdulbaqi Toyin; Bolaji, Hameed Olalekan (International Journal of Universal Education, 2024)
The study examined the challenges of Information and Communication Technology (ICT) tools for managerial functions among private secondary school administrators in Ilorin metropolis, Kwara State, Nigeria. Both primary and secondary data were used in the paper. Using a standardized questionnaire, the principals of the private secondary schools in the Ilorin Metropolis provided the data. The total population of Private Secondary Schools within Ilorin Metropolis is 141. The entire population was used as a sample for the study. Findings from the study showed that the majority of the respondents strongly disagreed that there is a non-availability of computers in private secondary schools. The respondents disagreed with the unavailability of internet services in the Ilorin metropolis. The majority of the respondents agree that inadequate Information and Communication Technology tools in private secondary schools. The study concluded that fear of technology use among principals, inadequate Information and Communication Technology tools, and power failure are the challenges confronting the effective use of ICT among principals in private secondary schools in the Ilorin metropolis. The paper recommended that the proprietors of private secondary schools in the Ilorin metropolis should procure more Information and Communication Technology tools. Computer literacy experts should be appointed as the principal. The management should introduce solar energy to save the school from the interrupted power supply.